Microalbuminuria in Patients with Diabetes Mellitus: Prevalence and Associated Risk factors Title of your - Zhian S. Ramzi; Mahfoodh A. Sulaiman (Kurdistan Journal of Applied Research, 2017)
Microalbuminuria is the most leading cause for cardiovascular disease, diabetic nephropathy, end stage renal diseases, and death among diabetic patients. The study carried out                                                                                       to find out the prevalence of microalbuminuria in a sample of Sulaimani diabetics and to determine its relation to different associated risk factors. The first part of study was a cross-sectional study conducted through examination of records of diabetic patients registered in Sulaimani Diabetic Center from June 2010 to May 2012. The second part was a case- control study that conducted in the same center, including 50 cases of diabetics with positive microalbuminuria, and 50 controls with negative one, that were registered in the same center and matched by age and gender. A specially designed questionnaire was used by researcher to collect information from the records. SPSS version 21.0 was used for data analysis. Males accounts for half of cases and controls, highest proportion of sample was found among age group (60-69) years about 34%. The prevalence of microalbuminuria was 29%. The study showed a statistical significant association of microalbuminuria with obesity, smoking, hypertension, retinopathy, ischemic heart disease, poor glycemic control, and dyslipidemia.  In conclusion moderate prevalence of microalbuminuria was found among diabetic patients, the prevalence was more common in poor glycemic control, and hypertensive diabetics. There was significant relation between microalbuminuria and diabetic nephropathy.